2008
DOI: 10.1177/1087057108326143
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Inhibitor Screening Platform via Mass Spectrometry

Abstract: Commonly used methods for isolated enzyme inhibitor screening typically rely on fluorescent or chemiluminescent detection techniques that are often indirect and/or coupled assays. Mass spectrometry (MS) has been widely reported for measuring the conversion of substrates to products for enzyme assays and has more recently been demonstrated as an alternative readout system for inhibitor screening. In this report, a high-throughput mass spectrometry (HTMS) readout platform, based on the direct measurement of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…For quantitative analysis of, for instance, HIV protease inhibitors, analysis times for a single spot on the target plate have been reported of $3 min for MALDI-FTICR MS (20 Hz laser), $30 sec for MALDI-TOF MS (50 Hz laser), and $5 sec for MALDI-triple quadrupole MS (1,000 Hz laser; van Kampen et al, 2006Kampen et al, , 2008aKampen et al, ,b, 2009b. Recently, an analysis time of 1.75 min for an entire 384-well target plate was reported for an assay to screen for small-molecule inhibitors of enzymes with MALDI-triple quadrupole MS (Rathore et al, 2008). When the time required for vacuum pump down was included, the total analysis time for a single target plate was still just under 3.5 min.…”
Section: A High-throughput Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…For quantitative analysis of, for instance, HIV protease inhibitors, analysis times for a single spot on the target plate have been reported of $3 min for MALDI-FTICR MS (20 Hz laser), $30 sec for MALDI-TOF MS (50 Hz laser), and $5 sec for MALDI-triple quadrupole MS (1,000 Hz laser; van Kampen et al, 2006Kampen et al, , 2008aKampen et al, ,b, 2009b. Recently, an analysis time of 1.75 min for an entire 384-well target plate was reported for an assay to screen for small-molecule inhibitors of enzymes with MALDI-triple quadrupole MS (Rathore et al, 2008). When the time required for vacuum pump down was included, the total analysis time for a single target plate was still just under 3.5 min.…”
Section: A High-throughput Analysismentioning
confidence: 98%
“…In MALDI-MS, however, the sample analysis time is primarily determined by the number of laser shots needed to generate an average mass spectrum of high quality and the repetition rate of the laser used. Dwell time of the ions does not contribute significantly to the analysis time, although the detection time of ions can take second(s) per scan in Fourier-transform ion cyclotron resonance (FTICR) MS and Orbitrap MS. With a high repetition rate laser that fires at 1,000-2,000 Hz, an averaged mass spectrum of high quality can be obtained in a few seconds with MALDI-time-of-flight (TOF) MS or MALDI-triple quadrupole MS (Hatsis et al, 2003;McLean, Russell, & Russell, 2003;Moskovets et al, 2006;Rathore et al, 2008). For quantitative analysis of, for instance, HIV protease inhibitors, analysis times for a single spot on the target plate have been reported of $3 min for MALDI-FTICR MS (20 Hz laser), $30 sec for MALDI-TOF MS (50 Hz laser), and $5 sec for MALDI-triple quadrupole MS (1,000 Hz laser; van Kampen et al, 2006Kampen et al, , 2008aKampen et al, ,b, 2009b.…”
Section: A High-throughput Analysismentioning
confidence: 99%
“…We demonstrated previously that MALDI-QqQ-MS technology has a great usability and is a versatile tool in the determination of concentrations (extra-and intracellular) of small molecules such as antiretroviral drugs (protease inhibitors), [14,15] anticancer drugs [13] but also other types of drugs [16 -18] and as screening tool in enzyme kinetic studies. [19] In a study by Volmer et al [20] the MALDI-QqQ-MS technology demonstrated equal performances compared with LC-QqQ-MS/MS instrumentation applying electrospray ionization (ESI) as ionization source when applied in pharmacokinetic studies. Previously, Notari et al [21,22] demonstrated that MALDI-TOF could be applied for the determination of low concentrations of antiretroviral drugs in plasma samples although concentrations of the antiretroviral drugs were not determined by isotope dilution mass spectrometry but by means of internal standard quantification.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] In the past several years, MS has been explored in primary screening for hit identification, including several methodologies in development for use in function-based biochemical reactions 1,5 and affinity-based binder screening (such as Dios-MS, 6 SpeedScreen, 7 and FAC-MS 8,9 ). Recently, approaches to further increase the analysis speed have been tested with matrix-assisted laser desorption/ionization (MALDI)-based MS technologies (e.g., MALDI-TOF-MS, 10 MALDI-QqQ-MS, 11 and MALDI-FTMS 12 ). However, many of the aforementioned approaches are still in proof-of-principle stages [10][11][12] or applied on relatively small-scale compound screening.…”
mentioning
confidence: 99%
“…Recently, approaches to further increase the analysis speed have been tested with matrix-assisted laser desorption/ionization (MALDI)-based MS technologies (e.g., MALDI-TOF-MS, 10 MALDI-QqQ-MS, 11 and MALDI-FTMS 12 ). However, many of the aforementioned approaches are still in proof-of-principle stages [10][11][12] or applied on relatively small-scale compound screening. 5,13,14 MS is still in its early stage for primary screening application.…”
mentioning
confidence: 99%